Mental health disabilities and human rights protections. (1st October 2015) - Szmukler, G.; Bach, M.
Abstract : Background: Around the world, reports regularly expose persistent and systemic human rights violations of patients in mental health services and facilities, and of those who are unable to access needed supports. A number of factors contribute – political will; the range and quality of services available; public and professional attitudes to mental health; stigma; health professionals' training and expertise; and available resources. Methods: This paper examines one of the main determinants, the legal framework. This sets the parameters for mental health policies and services and for applicable human rights norms and standards that can be realized in practice. Results: We provide an overview of international human rights instruments in relation to mental health disabilities, and of the major human rights violations in this area. Key implications for mental health law reform are drawn with a particular focus on discrimination and coercive interventions. The major challenges posed by the UN Convention on the Rights of Persons with Disabilities (2006) are examined. Current mental health laws, to greater or lesser degrees, fail to meet the newly required standards. We discuss reforms based on 'generic law' and 'legal capacity' principles that seek to meet those standards. Conclusions: We outline some emergent and promising examples of reform. The role of civil society and the importance of the standing of those with mental health disabilities in this process is noted.